Infrastructure inequality: Who pays the cost of road roughness? - Edward L. Glaeser; Lindsey Currier; Gabriel E. Kreindler (American Enterprise Institute (AEI), 2024)
Which Americans experience the worst infrastructure? What are the costs of living with that infrastructure? We measure road roughness throughout America using vertical acceleration data from Uber rides across millions of American roads. Our measure correlates strongly and positively with other measures of road roughness where they are available, negatively with driver speed, and we find road repair events decrease roughness and increase speeds. We measure drivers' willingness-to-pay to avoid roughness by measuring how speeds change with salient changes in road roughness, such as those associated with town borders and road repaving events in Chicago. These estimates suggest the roughness of the median local road in the US generates welfare losses to drivers of at least 31 cents per driver-mile. Roads are worse near coasts, and in poorer towns and in poorer neighborhoods, even within towns. We find that a household that drives 3,000 miles annually on predominantly local roads will suffer 318 per year more in driving pain if they live in a predominantly Black neighborhood than in a predominantly White neighborhood. Road roughness modestly predicts subsequent road resurfacing in New York City, but not in three other cities, which suggests that repaving is only weakly targeted towards damaged roads. Surveys from 120 towns and cities across the US suggests many reasons why resurfacing seems to be weakly targeted.
Keywords: 330; Infrastructure policy; Urban Policy